Tremorsoft: An Decision Support Application for Differential Diagnosis Between Parkinson S Disease and Essential Tremor - Chana-Cuevas, P (Elsevier B.V., 2023)
A cost-effective, non-invasive, and easy-to-use tool is presented that uses the 6-axis inertial sensor of the smartphone or a specific wearable sensor, boosted by machine learning, to support early differential diagnosis of Parkinson s disease and Essential Tremor. A dedicated web server helps extract the kinematic indexes from the recorded signals, implement the machine learning models and return the resulting classification to the App. Thus, clinicians can use this App as a support tool in the clinic, contributing to performing motor evaluations in the uncertain and undecided stages of the diseases and promoting appropriate, fast, and timely therapeutic responses. © 2023 The Authors